Dialectic of Tradition’s Strength and Demand for Flexibility: A Study of Minang Families in Yogyakarta - Jufri Naldo; Azhari Akmal Tarigan; Umar Warfete (JSW (Jurnal Sosiologi Walisongo), 2023)
The strong Minang family traditions are facing the demand for flexibility from modern city life, especially when Minang people live outside the Minang land, such as in Yogyakarta. This study aims to reveal how the ‘flexible life’ is experienced by Minang families. The questions are how family traditional provisions have fared and how Minang families in Yogyakarta accommodate traditional provisions in different social and cultural contexts. This study applies qualitative methods and a phenomenological approach involving 15 informants. The findings show that Minang families in Yogyakarta have seen changes in their marriage traditions, which used to be strictly regulated by Minangkabau custom. By opening a dialectical process in Yogyakarta, they accommodate and adapt to the Javanese traditions and customs in conducting marriages. The impact is that family marriage traditions change. Nonetheless, Minang families in Yogyakarta have not lost their Minang identity. They remain Minang even though they marry a non-Minang.